Role of Breakfast in Modulating Cognitive Attention through Glucose Metabolism: A Literature Review - Herlia, Renata Zhafira Putri; Hermawati, Luluk; Husna, Firda Asma’ul; Munifatuzzahra, Munifatuzzahra; Kusuma Wardani, Rizky (BALE LITERASI, 2026)
Breakfast is an essential daily meal that plays a key role in supporting both metabolic and cognitive functions. Glucose, as the brain’s primary energy source, is crucial for maintaining attention, memory, and executive function through neuronal activity and neurotransmitter regulation. This review aims to explore how breakfast consumption influences cognitive attention through mechanisms related to glucose metabolism. A narrative review approach was employed, drawing on literature from PubMed, Scopus, and Google Scholar published between 2015 and 2026. The findings indicate that eating breakfast helps restore and stabilize blood glucose levels after an overnight fast, thereby supporting cognitive performance—particularly in children and young adults. In addition, the quality and nutritional composition of breakfast, especially meals with a low glycemic index, contribute to more stable glucose levels and sustained cognitive function. In contrast, skipping breakfast has been associated with reduced attention and poorer mental performance. Overall, maintaining a regular and well-balanced breakfast appears to be an important factor in supporting cognitive function through effective glucose regulation, with meaningful implications for brain health and cognitive performance.